2022
DOI: 10.3390/ijms231810698
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Biochemical Regulation Mechanism of Exogenous Hydrogen Peroxide in Alleviating NaCl Stress Toxicity in Tartary Buckwheat (Fagopyrum tataricum (L.) Gaertn)

Abstract: We aimed to elucidate the physiological and biochemical mechanism by which exogenous hydrogen peroxide (H2O2) alleviates salt stress toxicity in Tartary buckwheat (Fagopyrum tataricum (L.) Gaertn). Tartary buckwheat “Chuanqiao-2” under 150 mmol·L−1 salt (NaCl) stress was treated with 5 or 10 mmol·L−1 H2O2, and seedling growth, physiology and biochemistry, and related gene expression were studied. Treatment with 5 mmol·L−1 H2O2 significantly increased plant height (PH), fresh and dry weights of shoots (SFWs/SDW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…The distinct clustering observed among all traits, particularly the identification of the XiNong 9943 genotype as exhibiting the highest drought tolerance. This result is consistent with prior research indicating the importance of RWC regulation, osmotic adjustment, and antioxidant defense mechanisms in conferring stress resilience [17,[65][66][67]. Overall, the integration of these analytical approaches enhances our understanding of genotypic responses to PEG-induced drought stress, elucidating key physiological and biochemical mechanisms underlying drought tolerance in Tartary buckwheat genotypes.…”
Section: Discussionsupporting
confidence: 89%
“…The distinct clustering observed among all traits, particularly the identification of the XiNong 9943 genotype as exhibiting the highest drought tolerance. This result is consistent with prior research indicating the importance of RWC regulation, osmotic adjustment, and antioxidant defense mechanisms in conferring stress resilience [17,[65][66][67]. Overall, the integration of these analytical approaches enhances our understanding of genotypic responses to PEG-induced drought stress, elucidating key physiological and biochemical mechanisms underlying drought tolerance in Tartary buckwheat genotypes.…”
Section: Discussionsupporting
confidence: 89%
“…Ion toxicity, osmotic imbalance, stunted plant growth, and deficiency in nutrient absorption occur in wheat grown in salt stress [ 46 ] It was also concluded that salt injury in plants is obvious in terms of decline in shoot growth, reduced leaf area, and decreased root zone [ 47 ]. A decrease in shoot branches, plant fresh and dry weight, and relative water content is reported in kiwi fruit under the influence of salt stress [ 48 ]. The deleterious impact of sodium and chloride ions is observed in brinjal grown under a soil-less system as well where a fewer number of leaves, yellowing of leaves due to salt, and decreased shoot growth are reported.…”
Section: Discussionmentioning
confidence: 99%
“…Ahmed et al reported that low concentrations of H 2 O 2 could induce the establishment of antioxidant defense mechanisms in crops [47]. Additionally, the use of exogenous H 2 O 2 could increase the tolerance of tomatoes, bell peppers, and watermelons to cold stress [48][49][50], improve the drought tolerance of soybeans, tobacco, and rapeseed [51][52][53], and improve the salt tolerance of wheat, tomatoes, and other crops [54][55][56][57]. Darmanti et al reported that under drought conditions, exogenous H 2 O 2 treatment enhanced the net photosynthetic rate and stomatal conductance of soybean leaves [58], while reducing the contents of the oxidative product malondialdehyde (MDA), which was induced by drought stress and H 2 O 2 .…”
Section: Effects Of Soil Moisture Content and Magnetoelectric Water O...mentioning
confidence: 99%